Establishing Logical Forms : What is assigned to what, how and why - Peregrin, Jaroslav; Svoboda, Vladimír (Logic and Logical Philosophy, 2023)
The paper presents a demarcation of a “minimalistic” concept of logical form, which nevertheless largely agrees with the way the term “logical form” is commonly used in contemporary logic and philosophy of logic. We see logical forms as formulas of formal languages assigned to (compounds of) sentences of a natural language (perhaps modulo notational variance). We thus reject the views of logical forms as underlying structures of thoughts or of the material reality that surrounds us. The assignment of the forms, we claim, aims at envisaging the logical (especially inferential) properties of the analyzed sentences, arguments, or other texts, as the analyzing formulas wear them, as it were, on their sleeves. Hence we suggest an “expressivist” and a pragmatic understanding of logical forms - they are used to expose (and fix) logical properties of sentences in textual contexts and the way of their employment is determined by the goals of the particular studies.